The future of education inspection in Andalucia: an alternative for progress - Orihuela Guerrero, José (Avances en Supervisión Educativa, 2014)
This report deals with the role that the educational inspection should play in the future, having in mind that we are living in a stratified society and consequently the education systems embrace different groups which, in many occasions, support opposite interests.In this sense, it is analyzed the legislative incontinence suffered by our pedagogic code and the lack of relation between the Administration and the Educational Communities, as well as, the inspection working conditions and its ancient organizational structure. For those reasons, we are going to defend not only a higher grade of independence and operational capacity, but also, the importance of decentralization, in the adoption of specific and concrete decisions.Advance of the Main Conclusions: The future proposal is related to the conception of the educational inspection as an educative changing agent and therefore, we are going to propose the placement of these professionals as a teaching character organ and as a dependent entity on the legislature, which should have a selection system based on a professional career and on a democratic system of internal organization.
Keywords: educational inspection; education system; educational change; organization and functioning